Adults with inflammatory bowel disease are at a greater risk of developing chronic rhinosinusitis: A nationwide population‐based study. (21st October 2020) - Lin, Yu‐Hsuan; Lin, Cheng Li; Kao, Chia‐Hung
Abstract: Background: Both inflammatory bowel disease (IBD) and chronic rhinosinusitis (CRS) are characterised by dysregulated immune responses. Though previous studies have demonstrated the coexistence of IBD and CRS, investigations of their association using large sets of epidemiologic data are lacking. Methods: We examined IBD and the subsequent risk of CRS in a nationwide setting. For 1 January 2000 to 31 December 2010, we identified in the National Health Insurance Dataset of Taiwan a total of 8313 patients over the age of 20 years with IBD. We randomly extracted 33 252 cases without IBD to create a comparison group matching patients by age, sex and index year. Cumulative incidences were obtained using the Kaplan‐Meier method, and we calculated risk estimates for the development of CRS using the Cox proportional hazards model. Results: In 295 007 person‐years, we identified 521 (1.25%) cases of IBD. The IBD cohort had a 1.26‐fold (95% confidence interval [CI], 1.17‐1.35) greater risk of developing CRS than the comparison group; for ulcerative colitis, it was 1.73‐fold (95% CI, 1.48‐2.05) and for Crohn's disease it was 1.20‐fold (95% CI = 1.11‐1.29). Subsequent analysis stratified by age revealed that the risk was highest among the population with IBD aged 50 to 64 years (adjusted hazard ratio = 1.37; 95% CI, 1.18‐1.59). A follow‐up‐specific analysis demonstrated that the risk appeared to be highest with a follow‐up duration of less than 2 years. Conclusion: The present analysis indicates that personal history of IBD, especially the phenotype ulcerative colitis, is associated with increased risk of subsequent CRS.